1995
DOI: 10.1590/1809-43921995252068
|View full text |Cite
|
Sign up to set email alerts
|

Observação Microscópica De Inclusões Minerais No Xilema De Espécies Tropicais Da Amazônia

Abstract: Foi investigada a distribuição de inclusões minerais (cristais e grãos de sílica) no xilema secundário de 53 famílias, representando 250 espécies de madeiras amazônicas. Grãos de silica ocorrem em cerca de 36% das espécies estudadas, frequentemente nas células dos raios. Cristais nas células dos raios são geralmente solitários, enquanto que nas fibras e células do parênquima axial são algumas vezes em cadeias cristalíferas. Os cristais são frequentemente do tipo prismático e somente em uma espécie (Scleronema … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Prismatic calcium oxalate crystals were observed in axial parenchyma cells of Caryocar villosum, in radial parenchyma cells of Protium altissimum, and both in Astronium lecointei. The presence of crystals is frequent in angiosperm wood and can be used as a taxonomic criterion in plant species, as well as in the analysis of difficulties encountered in wood processing (Vasconcelos et al 1995;Costa et al 2006). These mineral inclusions were previously cited in the literature by Nisgoski et al (2012) and Braga J unior et al (2020) for Caryocar villosum, by Albuquerque (2012) for Astronium lecointei, and by Ishiguri et al (2003) for Protium altissimum.…”
Section: Anatomical Featuresmentioning
confidence: 99%
“…Prismatic calcium oxalate crystals were observed in axial parenchyma cells of Caryocar villosum, in radial parenchyma cells of Protium altissimum, and both in Astronium lecointei. The presence of crystals is frequent in angiosperm wood and can be used as a taxonomic criterion in plant species, as well as in the analysis of difficulties encountered in wood processing (Vasconcelos et al 1995;Costa et al 2006). These mineral inclusions were previously cited in the literature by Nisgoski et al (2012) and Braga J unior et al (2020) for Caryocar villosum, by Albuquerque (2012) for Astronium lecointei, and by Ishiguri et al (2003) for Protium altissimum.…”
Section: Anatomical Featuresmentioning
confidence: 99%
“…The chemical composition was confirmed by SEM, which identified in the crystal the presence of silica (Si), oxygen (O 2 ), and carbon (C). According to Vasconcellos et al [33], the presence of silica in tropical woods is common and, for Burseraceae family, silica is exclusively found in fibers.…”
Section: Image Analysismentioning
confidence: 99%
“…(BURGER; RICHETER, 1991). Vasconcelos et al, (1993) reported that species of the genus Couratari present high silica content, at the point that the process to obtain sawn wood from trunk could be harmed, because of the abrasive effect on the cutting tools.…”
Section: Spectral Behavior In the Visible Region Of The Electromagnetmentioning
confidence: 99%